2020
DOI: 10.18632/oncotarget.27544
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging reveals biodistribution of P-cadherin LP-DART bispecific and trafficking of adoptively transferred T cells in mouse xenograft model

Abstract: P-cadherin-LP-DART is a bispecific antibody targeting P-cadherin expressed on the tumor cells and CD3 on the T-cells. Previously we demonstrated the development and efficacy of P-cadherin-LP-DART in in vitro and in vivo models. Here, we evaluated the three pillars: exposure, targeting specificity and pharmacodynamic modulation for P-cadherin-LP-DART using fluorescence molecular tomography (FMT). Bispecific antibodies and T-cells were conjugated with a near-infrared fluorophores: VivoTag ® 680XL (VT680) and Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…These findings suggest that a certain number of pre-existing T cells in the tumor is essential for initial inflammation and subsequent peripheral T cell recruitment. Supporting this idea, we performed simultaneous in vivo imaging of a T-BsAb and T cells as in the aforementioned system [66] and confirmed that peak T cell accumulation occurred after the T-BsAb was delivered to the tumor (data not shown). Our results revealed that the T-BsAb first contacted the tumor cells and then brought in peripheral T cells.…”
Section: Redirection Of Antitumor Immunitymentioning
confidence: 59%
See 1 more Smart Citation
“…These findings suggest that a certain number of pre-existing T cells in the tumor is essential for initial inflammation and subsequent peripheral T cell recruitment. Supporting this idea, we performed simultaneous in vivo imaging of a T-BsAb and T cells as in the aforementioned system [66] and confirmed that peak T cell accumulation occurred after the T-BsAb was delivered to the tumor (data not shown). Our results revealed that the T-BsAb first contacted the tumor cells and then brought in peripheral T cells.…”
Section: Redirection Of Antitumor Immunitymentioning
confidence: 59%
“…The authors labeled isolated T cells and their T-BsAb with two separate dyes that fluoresced at different wavelengths in order to distinguish between antibodies and T cells. They observed co-localization of their T-BsAb and T cells in tumors, and fluorescent signals from T cells peaked at 192 h after T-BsAb administration [66]. While these reports indicated an increased T cell quantity within tumors using in vivo imaging systems, several mechanistic studies have been performed to elucidate the cellular and molecular mechanism of the events involved.…”
Section: Redirection Of Antitumor Immunitymentioning
confidence: 99%
“…We have previously shown that FMT imaging aids understanding of the three pillars of drug development: targeting/distribution, binding to the target, and the expression of pharmacology. 30 , 31 In this study, we again used FMT to demonstrate that the anti-IL13Rα2 Ab was able to target IL13Rα2-expressing tumors, exhibited favorable PK characteristics that are consistent with full-length antibodies, and that anti-IL13Rα2-ADC with an auristatin payload exhibited in vitro and in vivo anti-tumor activity. Since FMT is restricted to use in preclinical imaging, we also studied the biodistribution and tumor targeting of anti-IL13Rα2-Ab by PET imaging, a modality that is readily translatable to the clinic.…”
Section: Discussionmentioning
confidence: 90%
“…P-cadherin constitutes an attractive target with therapeutic potential to treat tumours that highly express this protein, with several studies addressing its target using different approaches [116][117][118][119]. In fact, for breast cancer, PCA062, a P-cadherin-targeting antibody-drug conjugate may have clinical potential, since it has been shown to have potent antitumour activity with acceptable efficacy and tolerability in preclinical studies in primates [120].…”
Section: Cadherin-3 (P-cadherin)mentioning
confidence: 99%
“…PF-06671008 is a CD3-bispecific molecule-targeting P-cadherin that was able to promote T-cell-mediated regression of established tumours in mice models. Importantly, PF-06671008 is already in phase I clinical trials (NCT02659631) for triple-negative breast cancer patients [118,121].…”
Section: Cadherin-3 (P-cadherin)mentioning
confidence: 99%